Depression a study in abnormal behaviour - CRM Educational Films (Del Mar, Calif. : CRM/McGraw-Hill Films, 1973)
This film is on abnormal behaviour, the viewer follows a young housewife-teacher through the course of a depressive episode. The pattern of abnormal behaviour becomes clear through watching the progress of Helen's inability to funtion normally.
Keywords: Depression, Mental; Neurotics; Mental health services